JOAQUÍN COSTA I REGENERACJA HISZPANII - Gołaszewska-Rusinowska, Dominika (Studia Europaea Gnesnensia, 2018)
This case study focuses on the life and work of Joaquín Costa. He was a Spanish intellectual who in late 19th century and early 20th century started the intellectual and political movement called Regenerationism. This movement emerged in response against the political system of Spanish Restoration.